Joint impact of phthalate exposure and stressful life events in pregnancy on preterm birth. (December 2019) - Ferguson, Kelly K.; Rosen, Emma M.; Barrett, Emily S.; Nguyen, Ruby H.N.; Bush, Nicole; McElrath, Thomas F.; Swan, Shanna H.; Sathyanarayana, Sheela
Highlights: Phthalate exposure as well as psychosocial stress have been associated with preterm birth. We categorized women based on stressful life events experienced in pregnancy (yes/no). Among stressed women, some phthalate metabolites were associated with preterm birth. In non-stressed women, we observed no associations. Phthalate and stress exposure in pregnancy may have a joint effect on preterm birth. Abstract: Background: Urinary phthalate metabolites and psychosocial stress in pregnancy have each been associated with preterm birth (PTB), but no study has examined the joint impact of these two environmental exposures. We hypothesized that there would be stronger associations between phthalate exposure and PTB in mothers with higher stress in pregnancy compared to mothers with lower stress. Methods: We addressed this question using data from The Infant Development and the Environment Study (TIDES), a prospective birth cohort conducted at four US sites (N = 783). We examined urinary phthalate metabolite concentrations measured in samples collected from up to three trimesters of pregnancy. Mothers reported their exposure to stressful life events (SLE) in each trimester in a questionnaire administered in the third trimester. PTB was defined as delivery before 37 weeks completed gestation (n = 71, 9.1%). We examined associations between urinary phthalate metabolite concentrations (individual time points and on average) and PTB using logistic regression models adjusted for maternal race, age, pre-pregnancy body mass index, education, specific gravity, and gestational age at sample collection. In addition, we created models stratified by whether or not mothers were exposed to any or no SLE in pregnancy. Results: Summed di-2-ethylhexyl phthalate (ΣDEHP) metabolites measured in urine samples from the third trimester, but not the first trimester, were associated with an increased odds ratio (OR) of PTB (OR = 1.44, 95% confidence interval [CI] = 1.06, 1.95). In models stratified by SLE, associations between third trimester ΣDEHP concentrations and PTB were significant only for women experiencing one or more SLE during pregnancy (OR for ΣDEHP: 2.09, 95% CI: 1.29, 3.37) but not for women with no SLE during pregnancy (OR for ΣDEHP: 1.04, 95% CI: 0.66, 1.63) (p for interaction = 0.07). Conclusions: We observed an association between urinary ΣDEHP levels and PTB that was modified by whether a mother was exposed to one or more psychosocial stressors during pregnancy. Additional research to understand the joint impacts of chemical and non-chemical exposures, with an emphasis on timing of exposure, is needed in order to advance the state of the science on how the environment influences pregnancy.